Light‐Emitting Diodes with Hierarchical and Multifunctional Surface Structures for High Light Extraction and an Antifouling Effect. Issue 2 (17th November 2015) - Leem, Young‐Chul; Park, Jung Su; Kim, Joon Heon; Myoung, NoSoung; Yim, Sang‐Youp; Jeong, Sehee; Lim, Wantae; Kim, Sung‐Tae; Park, Seong‐Ju
Abstract : Bioinspired hierarchical structures on the surface of vertical light‐emitting diodes (VLEDs) are demonstrated by combining a self‐assembled dip‐coating process and nanopatterning transfer method using thermal release tape. This versatile surface structure can efficiently reduce the total internal reflection and add functions, such as superhydrophobicity and high oleophobicity, to achieve an antifouling effect for VLEDs.